Situation-Aware Access Control in Federated Data-as-a-Service for Maritime Search and Rescue - Oni, Samson; Chen, Zhiyuan; Crainiceanu, Adina; Joshi, Karuna; Needham, Don (IEEE, 2019)
Maritime Search and Rescue missions involve complex operations in which multiple entities, playing different roles in dynamic situations, benefit from sharing mission-dependent data. We propose an approach to support situation-aware access control in a federated Data-as-a-Service architecture. We develop an ontology and rules to represent access control policies and a distributed reasoning framework to enforce these policies. We implement our proposed solution in a proof-of-concept system.
2019 IEEE International Conference on Services Computing (SCC), 8-13 July 2019, Milan, Italy.
Keywords: UMBC Ebiquity Research Group